Implantation of Impella CP left ventricular assist device under the guidance of three-dimensional intracardiac echocardiography - Yastrebov, Konstantin (Sci Rep, 2020)
Impella CP is a percutaneously inserted left ventricular assist device indicated for temporary mechanical cardiac support during high risk percutaneous coronary interventions and for cardiogenic shock. The potential application of Impella has become particularly relevant during the current COVID-19 pandemic, for patients with acute severe heart failure complicating viral illness. Standard implantation of the Impella CP is performed under fluoroscopic guidance. Positioning of the Impella CP can be confirmed with transthoracic or transoesophageal echocardiography. We describe an alternative approach to guide intracardiac implantation of the Impella CP using two-dimensional and three-dimensional intracardiac echocardiography. This new technique can be useful in selected groups of patients when fluoroscopy, transthoracic and transoesophageal echocardiography is deemed inapplicable or limited for epidemiological or clinical reasons. Intracardiac three-dimensional echocardiography is a feasible alternative to the traditional techniques for implantation of an Impella CP device but careful consideration must be given to the potential limitations and complications of this technique.